PEMANFAATAN LIMBAH BATANG JAGUNG SEBAGAI PUPUK ORGANIK DI DESA KUNGKILAN - Nurshanti, Dora Fatma; Ogari, Putri Ayu; Al Hadad, Muhamad; Astuti, Elis Yuni; Sera, Belta; Lorenza, Dina (Penerbit Widina, Widina Media Utama, 2025)
This Community Service Program was conducted in Ogan Komering Ulu Regency, Kungkilan Village, Sosoh Buay Rayap District, , in August 2025. The purpose of this activity was to empower farmers in processing corn stalk waste into organic fertilizer. The methods used included lectures, discussions, and practical simulations of organic fertilizer production. The activities began with providing theoretical material on the benefits of corn stalks and composting methods, followed by practical exercises on making organic fertilizer. This program involved 25 farmers as participants, who were the target partners in the village. Evaluation results showed a 40% increase in knowledge, with an improvement in understanding the benefits of corn stalks from 45% to 85%, using pre-test and post-test questionnaires. The composting techniques from 50% to 90%, and the impact of organic fertilizer on agricultural yields from 40% to 80%. The program also successfully reduced farmers' dependence on chemical fertilizers, with 60% of farmers reporting a decrease in chemical fertilizer usage and 75% of farmers starting to process corn stalks into organic fertilizer. This activity also supported environmentally friendly farming practices by reducing the burning of agricultural waste and improving farmers' welfare. Overall, this program successfully achieved its objectives and has the potential to be implemented in other areas.ABSTRAKProgram Pengabdian kepada Masyarakat ini dilaksanakan di Kabupaten Ogan Komering Ulu tepatnya pada Desa Kungkilan, Kecamatan Sosoh Buay Rayap, pada bulan Agustus 2025. Tujuan dari kegiatan ini adalah untuk memberdayakan petani dalam mengolah limbah batang jagung menjadi pupuk organik. Metode yang digunakan meliputi ceramah, diskusi, dan simulasi praktis pembuatan pupuk organik. Tahapan kegiatan dimulai dengan pemberian materi teori mengenai manfaat limbah jagung dan cara pengolahan kompos, diikuti dengan praktik langsung pembuatan pupuk organik. Program ini melibatkan 25 petani sebagai peserta, yang merupakan mitra sasaran di desa tersebut. Hasil evaluasi menunjukkan peningkatan pengetahuan sebesar 40%, dengan pemahaman manfaat limbah jagung meningkat dari 45% menjadi 85%, melalui kuesioner pre-test dan post-test. teknik pengolahan kompos dari 50% menjadi 90%, dan pengaruh pupuk organik terhadap hasil pertanian dari 40% menjadi 80%. Program ini juga berhasil mengurangi ketergantungan petani pada pupuk kimia, dengan 60% petani melaporkan pengurangan penggunaan pupuk kimia dan 75% petani mulai mengolah limbah jagung menjadi pupuk organik. Kegiatan ini juga mendukung pertanian ramah lingkungan dengan mengurangi pembakaran limbah, serta meningkatkan kesejahteraan petani. Secara keseluruhan, kegiatan ini berhasil mencapai tujuannya dan berpotensi diterapkan di wilayah lain.